2018
DOI: 10.2147/ijwh.s181557
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of feminine identity: the strategies of women with breast cancer to cope with body image altered

Abstract: BackgroundBody image altered is the most important psychosocial concern associated with breast cancer. Yet, there is a paucity of information regarding strategies for coping with this problem. This study aimed to explore Iranian breast cancer women’s strategies for coping with body image altered.MethodsThis qualitative study was conducted in 2016–2017. A purposive sample of 36 women with breast cancer was selected with maximum variation from three health care centers in Alborz Province, Iran. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…In this study, some Chinese BCSs emphasized that their body changes, fear of relapse, and rejection from others were also the sources of stress. Similar findings were reported in another study that body change can bring stress to the survivors, and it also mentioned BCSs used makeup, hairpiece and breast reconstruction to conceal their physical defects [ 34 ]. Therefore, our findings add to the strong evidence of the important role of therapists’ professional psychological counseling.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, some Chinese BCSs emphasized that their body changes, fear of relapse, and rejection from others were also the sources of stress. Similar findings were reported in another study that body change can bring stress to the survivors, and it also mentioned BCSs used makeup, hairpiece and breast reconstruction to conceal their physical defects [ 34 ]. Therefore, our findings add to the strong evidence of the important role of therapists’ professional psychological counseling.…”
Section: Discussionsupporting
confidence: 84%
“…Body image is a complex post-treatment concern, especially for younger women with breast cancer (Paterson et al, 2016). Recovery of body image after mastectomy is essential for the physical and mental quality of life (Marín-Gutzke and Sánchez-Olaso, 2010;Zeighami Mohammadi et al, 2018) and for regained emotional wholeness (Howes et al, 2016;Siqueira et al, 2020). In addition, the finding that after reconstruction the younger participants felt like women again, with improved appearance and sexuality, agrees with previous studies (Fallbjork et al, 2012;Panchal and Mathos, 2017).…”
Section: Body Image Loss Of Femininity and Sexualitysupporting
confidence: 85%
“…Breast loss caused by mastectomy is considered by many women as a serious blow to their self-identity and feelings (Przezdziecki et al, 2013). Therefore, many women lose their femininity and selfconfidence after losing their breasts due to mastectomy (Sabo & Thibeault, 2012;Zeighami Mohammadi et al, 2018). Improving appearance is one of the main strategies used by participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that women in British Columbia use make-up, prosthesis, wigs, scarves, veils, tattoos, and breast reconstruction to conceal or correct their physical defects (Zeighami Mohammadi et al, 2018). Physical changes make women feel limited control over their physical appearance, thus making them frustrated and anxious and undermining their self-confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation